Evaluation of knowledge, attitude and practice of Tabriz's school health workers about oral and dental health - Taghizadeh Ganji A.; Jafari A.; Poorgholi N.; Iranizadeh H. (Tehran University of Medical Sciences, 2009)
"nBackground and Aim: School health workers have an important role in education and prevention of common oral and dental diseases. An organized program can be helpful in training and shaping the proper behavior. This study has evaluated the knowledge, attitude and practice of schools health workers in Tabriz about oral and dental health in 2007-2008."nMaterials and Methods: This cross-sectional and descriptive study was performed in primary schools in Tabriz. Questionnaires were sent to the schools that had health workers. Levels of the knowledge, attitude and practice of the health workers who had answered this questionnaire were evaluated. SPSS software and independent T-Test and Paired- Sample T-Test were used for analyzing the results."nResults: Fifty eight out of 64 school health workers were women. Mean age of school health workers was 45 years. Forty four of school health workers had passed special course about oral health and dental health. 49 of them had passed special educational course the mean of acquired knowledge score was 6.77 out of 10 and women's scores were significantly higher. Also women had more work experience than men. The mean of acquired attitude and practice scores were 7.42 and 7.14 out of 10, respectively."nConclusion: Findings show that performing of the educational courses during work and experience has an effective role in the scales of the health workers. Progress in this situation can be achieved by retraining programs and accessible pamphlets.